Little Lindy is kidnapped : how the media covered the crime of the century - Doherty, Thomas (Columbia University Press, 2020)
The biggest crime story in American history began on March 1, 1932, when the twenty-month-old child of Charles and Anne Lindbergh was snatched from his crib in Hopewell, New Jersey. The news shocked a nation enamored of the famous aviator, the first to fly solo nonstop across the Atlantic. Virtually every police officer in the area was dispatched to return 'Little Lindy' to the arms of his parents'and perhaps even more energized were the legions of journalists catering to a public whose appetite for Lindbergh news was insatiable. In Little Lindy Is Kidnapped, Thomas Doherty offers a lively and comprehensive cultural history of the media coverage of the abduction and its aftermath. Beginning with Lindbergh's ascent to fame and proceeding through the trial and execution of the accused perpetrator, Doherty traces how newspapers, radio, and newsreels reported on what was dubbed the 'crime of the century.' He casts the kidnapping as a transformative moment for American journalism, analyzing how the case presented new challenges and opportunities for each branch of the media in the days before the rise of television. Coverage of the Lindbergh story, Doherty reveals, set the script for the way the media would treat breaking news for decades to come. An engrossing account of one of American history's most breathlessly covered cases, Little Lindy Is Kidnapped sheds new light on an enduring quality of journalism ever since: the media's eye on a crucial part of the story'itself.